The Effect of Contextual Learning Strategies on the Ability to Write Poetry For Grade VIII Students of MTSN Tanjungbalai - Fahliza Syahira; Budiman Budiman (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study aims to determine the effect of contextual learning strategies (CSLS) on the poetry writing skills of eighth-grade students at MTsN Tanjung Balai. The study used a quantitative approach with experimental methods and design.pretest-posttest control groupThe study population consisted of 320 students spread across 10 classes. The study sample consisted of two classes: class VIII-1 as the experimental class implementing SPK and class VIII-4 as the control class using expository learning strategies. Data collection was conducted through a poetry writing ability test, then analyzed using statistical techniques to test the effect of the treatment. The results showed that the average score of students' poetry writing ability at thepretestwas 67.81, while the average value of the experimental class after the implementation of SPK increased to 77.50. The results of the analysis also showed that contextual learning strategies had a significant effect on the poetry writing ability of grade VIII students at MTsN Tanjung Balai. The implications of this study indicate that contextual learning strategies can be used as an effective learning alternative to improve poetry writing skills because they are able to connect material with students' real experiences, thereby encouraging creativity, imagination, and the ability to express ideas in the form of poetry.